2014
DOI: 10.1002/anie.201408108
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Nanocrystals of Lithiated Group 14 Elements

Abstract: The synthesis of colloidal nanocrystals (NCs) of lithiated group 14 elements (Z=Si, Ge, and Sn) is reported, which are Li4.4 Si, Li3.75 Si, Li4.4 Ge, and Li4.4 Sn. Lix Z compounds are highly reactive and cannot be synthesized by existing methods. The success relied on separating the surface protection from the crystal formation and using a unique passivating ligand. Bare Lix Z crystals were first produced by milling elemental Li and Z in an argon-filled jar. Then, under the assistance of additional milling, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
(228 reference statements)
0
8
0
Order By: Relevance
“…2, 3 Among dozens of substitutions, silicon is an extremely competitive candidate owing to various advantages such as the abundance, safety, environmental friendliness, low operation potential (˂0.5 V vs. Li/Li + ) and in particular, the ever-known highest theoretical capacity (~4200 mAh g -1 , for Li 22 Si 5 alloys). [4][5][6] On the other hand, it simultaneously suffers from troublesome shortcomings, including the sluggish diffusivity for Li + ions (1.9×10 -14 cm 2 s -1 ), 7 intrinsically low electric conductivity (1.6×10 -3 S m -1 ) 8 and in particular, huge volume variations (>400%) leading to the gradual cracking, pulverization, electrical disconnection, unstable solid electrolyte interphase (SEI) films, and resultantly a rapid capacity fading. To approach these issues mentioned above, great efforts have been made in both the external and internal aspects.…”
Section: Preparation and Lithium Storage Performance Of Yolk-shell Simentioning
confidence: 99%
“…2, 3 Among dozens of substitutions, silicon is an extremely competitive candidate owing to various advantages such as the abundance, safety, environmental friendliness, low operation potential (˂0.5 V vs. Li/Li + ) and in particular, the ever-known highest theoretical capacity (~4200 mAh g -1 , for Li 22 Si 5 alloys). [4][5][6] On the other hand, it simultaneously suffers from troublesome shortcomings, including the sluggish diffusivity for Li + ions (1.9×10 -14 cm 2 s -1 ), 7 intrinsically low electric conductivity (1.6×10 -3 S m -1 ) 8 and in particular, huge volume variations (>400%) leading to the gradual cracking, pulverization, electrical disconnection, unstable solid electrolyte interphase (SEI) films, and resultantly a rapid capacity fading. To approach these issues mentioned above, great efforts have been made in both the external and internal aspects.…”
Section: Preparation and Lithium Storage Performance Of Yolk-shell Simentioning
confidence: 99%
“…Owing to its technical importance, numerous experimental and theoretical studies have been carried out to understand the structure, stability, and mechanical and electrical properties of phases in this system . Li–Si compounds were also directly used as prelithiated anode materials . However, in situ X‐ray diffraction (XRD) studies on the lithiation/delithiation of Si anodes confirmed the absence of the above‐mentioned stable compounds in the electrochemical reaction in Li‐ion batteries at room temperature .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of particle size down to the nanometer scale could effectively shorten diffusion paths for hydrogen and mass transport, increase the surface‐to‐volume ratios of particles, and improve the interfacial reactivity during reversible hydrogen storage reactions, leading to significantly improved hydrogen storage performance . Among them, lithium metal and/or its hydrides are the major constituents, which could be directly used as precursors for oxygen‐free lithiation of various composites, but their chemical synthesis still remains a big challenge owing to their high reactivity and incompatibility with all conventional ligands, and it becomes the more challenging, the smaller the particles are . Moreover, nanostructured particles are intrinsically unstable and tend to grow into larger crystallites, which would result in continuous degradation of the nanostructure‐induced improvement of hydrogen storage performance .…”
mentioning
confidence: 99%